Frontier Warfare in the Argentine Pampas From An Archaeological Perspective: Late XIXth Century Military Sites in Carlos Casares County, Buenos Aires Province, Argentina - Leoni, Juan Bautista (2018)
Throughout the XIXth century, a process of territorial expansion developed in what is now Argentina. Initiated under the Spanish rule, it deepened after independence in 1816. It sought to incorporate extensive tracts of land in the region known as the Pampas, vast treeless plains with a temperate climate. These lands were favorable for cattle raising and agriculture and thus indispensable for an economy oriented toward the export of primary commodities. This expansion, however, was an uneven process, heavily dependent on the political and economic consolidation of the Argentine society, and especially on the building of a modern nation-state, which only began after 1861. Thus, the final accomplishment of this territorial goal could only be completed after a massive military campaign in 1879.